2021
DOI: 10.1111/1462-2920.15515
|View full text |Cite
|
Sign up to set email alerts
|

A simple, switchable pili‐labelling method by plasmid‐based replacement of pilin

Abstract: Summary Labelling of Type IV pili (TFP) can greatly improve our understanding of the pivotal roles of TFP in a variety of bacterial activities including motility, surface sensing and DNA‐uptake etc. Here we show a simple and switchable pili‐labelling method by plasmid‐based inducible replacement of PilA without genetic modification in bacterial genome employed by complicated methods. Using this method, we characterized pili morphology and twitching motility of Pseudomonas aeruginosa in details. More importantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(20 citation statements)
references
References 41 publications
(82 reference statements)
3
17
0
Order By: Relevance
“…By directly tracking the movement of cells with fluorescent TFP, we found that Syn7942-PilAm cells can perform twitching by extension-retraction cycles of TFP. The extension and retraction rates of TFP were 0.69 ± 0.08 and 0.43 ± 0.03 μm/s, respectively, which are faster than those of P. aeruginosa ( 18 ). Although the mechanism may be similar to the twitching motility observed in other bacteria ( 19 , 20 ), Syn7942-PilAm displayed richer surface movement modes.…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations
“…By directly tracking the movement of cells with fluorescent TFP, we found that Syn7942-PilAm cells can perform twitching by extension-retraction cycles of TFP. The extension and retraction rates of TFP were 0.69 ± 0.08 and 0.43 ± 0.03 μm/s, respectively, which are faster than those of P. aeruginosa ( 18 ). Although the mechanism may be similar to the twitching motility observed in other bacteria ( 19 , 20 ), Syn7942-PilAm displayed richer surface movement modes.…”
Section: Resultsmentioning
confidence: 86%
“…To directly visualize the behavior of TFP, we replaced an amino acid residue of the major pilin subunit PilA with a Cys for subsequent labeling with a thiol-reactive fluorescent maleimide dye ( 18 ). In detail, without changing the original pilA ( S ynpcc7942_0048 ) of Syn7942 wild type (hereafter Syn7942-WT), we overexpressed the mutated cassette encoding PilAm (PilA with S87C) with a strong promoter p cpc560 at the neutral site NSI (fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results (Figure ) show that Δ pilT has a larger area density of attached cells ((2.0 ± 0.2) × 10 –2 μm –2 ) than WT, suggesting that more and longer TFP are beneficial for cell attachment to the oil–water interface, whereas Δ pilA has a similar level ((1.2 ± 0.3) × 10 –2 μm –2 ) as WT, which seems to contradict the results of Δ pilT . This seemingly contradicting result of Δ pilA is probably caused by the degree of piliation of cells, as a WT cell typically has just one or two pili distributed at one pole of the cell, which is phenotypically not very different from that of Δ pilA in terms of the degree of piliation.…”
Section: Resultsmentioning
confidence: 93%